Character Training and Personal Resilience in the Student Regiment of Ahmad Dahlan University, Yogyakarta - Zul Fadhli Sultani (Yayasan Al-Afif, 2025)
Students who are involved in organizations tend to experience problems or challenges in interacting with their campus environment. These problems or challenges need to be addressed by participating in organizational activities, especially the Student Regiment. The purpose of this study is to examine the role of the Student Regiment (MENWA) in shaping students’ personalities and fostering personal resilience. This study took place at Ahmad Dahlan University, an object within the scope of the MENWA organization. The method used in this study is a qualitative method with a descriptive approach. The descriptive approach is intended to measure the social phenomenon of the student regiment accurately. The data collection techniques and tools used by the author in this study were interviews, observations, and documentation presentations. The results of the study indicate that by participating in MENWA organizational activities, personal characters are formed that are disciplined, honest, responsible, brave to appear and agile. These characters reflect personal resilience that is able to create a mutually supportive environment and foster a sense of kinship with one another. The conclusion shows that MENWA UAD can be a forum for cultivating good character and strengthening students’ personal resilience.